Hubungan Antara Penerimaan Diri Lansia Dengan Angka Harapan Hidup Di Kelurahan Wates Kota Mojokerto - Yusuf Hariadi (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2014)
Based on the survey from BPS Mojokerto City, life expectancy is increased every year. The increased of life expectancy should be caused by highly self acceptance. But at Wates Distrik Magersari Mojokerto City, self acceptance of elderly was negative. This research aims to know the relation between elderly self acceptances with life expectancy at Wates Distrik Magersari Mojokerto City. Research design was ex post facto with retrospective study approach. The independent variable was self acceptance of elderly and the dependent variable was life expectancy. Population is all the elderly who had died in 2012 and their family at Wates Distrik Magersari Mojokerto City as many as 12 people and obtained 12 elderly as sample by using purposive sampling. Data were taken using a questionnaire for the independent variables and the death table lists for dependent variable. Then data were analyzed by Fisher Exact Test. The result showed from 5 respondents who have higher life expectancy, mostly 4 (33,3%) respondents have positive self acceptance and 1 (8,3%) respondent has negative self acceptance, and then from 7 respondents who have lower life expectancy, all of them have negative self acceptance. The result of Fisher Exact Test showed p value = 0,010 < Î± (0,05), so H0 was rejected and H1 was accepted means there is a relation between elderly self acceptances with life expectancy at Wates Distrik Magersari Mojokerto City. Negative self acceptance could lead to lower life expectancy due to poor in fulfilling life needs and self realization, thus it reduced life satisfaction and also happiness. The given of information should be increased about the importance of mentally health, especially on self acceptance.